Diagnostic Accuracy of Mammography and Ultrasonography Screening for Breast Cancer in Pregnant and Lactating Women: Accuracy of Breast Cancer Screening in Pregnancy - Mujahid, Naima; Anwar, Wajeeha; Usman, Fareeha; Hafeez, Sana; Bhatti, Shaista; Abideen, Zen Ul (Pakistan Journal of Health Sciences, 2024)
Breast cancer was of significant health concern affecting women worldwide. Objective: To assess diagnostic accuracy of mammography and ultrasonography in differentiating malignant and benign breast lesions in pregnant and lactating women. Methods: A cross sectional retrospective study was conducted at Radiology department of Shahida Islam Medical Complex, Lodhran from May 2023 to April 2024. A sample size of 242 females was calculated. Electronic medical records were reviewed for radiological examination including screening ultrasound and mammography. All those pregnant and lactating females on which ultrasound and mammograms were performed were included. SPSS version 23.0 was used for data analysis. Diagnostic accuracy of both ultrasound and mammography were calculated in terms of malignant or benign and sensitivity and specificity. Mann-Whitney U test was applied between mammography, ultrasonography and BI-RADS categories. Results: Of 242 females, 110 underwent mammography and 132 underwent ultrasound. Negative mammography was observed in 71 females in which at biopsy, 24 were benign. Negative ultrasound with only benign lesion was seen in 68 females and 10 of which were confirmed at biopsy. Specificity of ultrasonography was 100 %, sensitivity 85.7 %, positive predictive value of 100 % while negative predictive value of 25 %. Specificity of mammography was 100 %, sensitivity 92.3 %, positive predictive value of 100 % while negative predictive value of 42.8 % (p<0.001). Conclusions: Although both ultrasound and mammography were found to be specific, use of mammography was considered better in terms of sensitivity and diagnostic accuracy.